UANG DAN KONSEP TIME VALUE OF MONEY DALAM PANDANGAN ISLAM - Pertiwi, Dian (J-ESA (Jurnal Ekonomi Syariah), 2019)
Money used in Islam is money that doesn’t not contain usury in its creation. The form can be full bodied money or fiat money with 100% gold standard. The principle of both is the same, namely limiting the creation of money so that the stability of the value of money is maintained. Current banknotes legally and in fact have become legitimate payment instrument. Its position is still a legitimate means of payment as long as it meets the conditions set by sharia, namely the government must declarat it as a legal payment instrument, the government must maintain its value, ensures that there is no trade in money and prohibits and prevents the circulation of counterfeit money. The concept of Time Value of Money is motivated by the presumption of the loss of capital owners of opportunity cost when they lend money to other parties, so that the capital owner imposes a certain precentage value as compensation to the borrower. The view of Islam is that money has no time value. But time has economic value, the value of time will be higher if someone can take advantage of his time. The more effective and efficient the higher the time value will be.